2014
DOI: 10.11606/issn.1981-0490.v17i1p17-32
|View full text |Cite
|
Sign up to set email alerts
|

Entre o não lugar e o protagonismo: articulações teóricas entre trabalho, gênero e raça

Abstract: Este artigo tem como objetivo analisar o entrelaçamento das categorias trabalho, gênero e raça, visibilizando os arranjos sociais responsáveis pela criação de um não lugar destinado a mulheres, negros e, particularmente, às mulheres negras. Para cumprir esta finalidade utilizamos dados quantitativos e qualitativos produzidos por institutos de pesquisas brasileiros e por pesquisadores da temática étnico-racial. A análise desses indicadores sociais reitera que o ambiente do trabalho é um espaço adverso à diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
3
0
12
Order By: Relevance
“…Race and gender make their mark on different social experiences and consolidate not only socioeconomic inequalities, but also symbolic and cultural inequalities. 20 In general, Brazilian women are more educated that compared to men, but their jobs and incomes fall short. In the case of white men and black women, there is an abyss between the occupations and incomes of both, leaving the black woman in situations of obvious disadvantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Race and gender make their mark on different social experiences and consolidate not only socioeconomic inequalities, but also symbolic and cultural inequalities. 20 In general, Brazilian women are more educated that compared to men, but their jobs and incomes fall short. In the case of white men and black women, there is an abyss between the occupations and incomes of both, leaving the black woman in situations of obvious disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…In view of these aspects, it is understood that the possibilities of access to financial and intellectual resources are linked to gender and race, as well as to the way these variables interact within and outside the labor market. 20 The second category refers to the ideas that recyclable materials collectors have about women's work, the existence of gender issues in the work environment and double working hours. Women workers recognized that there are differences in recognition and salary when compared to men, which highlights the fact that the participants recognize the existence of gender issues at work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the studied mothers understand they need to first fulfill the daily domestic demands. In agreement to these data, a study performed in São Paulo, Brazil, indicated that women end up spending more time with house maintenance and feeding functions (20) .…”
Section: Discussionmentioning
confidence: 55%
“…Como consequência desse acúmulo de tarefas, além do desgaste, observa-se o impacto na esfera econômica e, consequentemente, na autonomia, fenômenos característicos de mais um dos mecanismos de restrição às mulheres (Santos, Diogo, & Shucman, 2014). Adota-se como referência os dados que demonstram que a inserção das mulheres no mercado de trabalho produtivo não significa a redução da jornada doméstica, mas um acréscimo, aumentando e intensificando seu tempo de labor, o que tende a se ampliar na presença de filhos (Dedecca, 2004).…”
Section: Tempo Livre?unclassified
“…Dentre os hábitos que se mantêm, destaca-se o trabalho feminino como uma das ferramentas mais importantes na continuidade das redes de relações sociais das sociedades rurais (Santos et al, 2014). Por meio dessas práticas, criam-se espaços de produções solidárias: hortas ao lado das casas, os pomares, as pequenas lavouras nos espaços onde a produção de caráter extensivo não alcança devido ao solo rochoso ou íngreme, enfim, onde são produzidos os alimentos para a família consumir e para a realização das trocas entre vizinhas.…”
Section: Tempo Da Vida Tecnologias E Sucessãounclassified